Technological progress and the theory of technological singularity - Stepanov, D. (ХНУРЕ, 2023)
The report discusses the purpose of technological progress, the theory of technological singularity and the modern element base of electronics. The advantages and risks of technology development are explored, the increasing complexity of electronic devices and systems, their vulnerability to cyber-attacks is emphasized. The theory of technological singularity and the potential transformative events that it can cause are considered in detail. It also touches upon the issue of e-waste disposal and the importance of proper disposal methods to minimize the environmental impact of electronic devices. Discusses the use of hardware to prevent cyberattacks and the e-waste business.